2015
DOI: 10.1002/2014jf003367
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian creeping mass of different grain sizes over sand beds of varying length

Abstract: Creep is an important mode of aeolian sand transport, but it has received little attention in previous studies due to experimental difficulties and insufficient theory. In this study, we conducted 116 groups of experiments with three repeats for each group in a wind tunnel to measure the creeping mass of four different mean grain sizes (152, 257, 321, and 382 μm) over six bed lengths (2.0, 3.5, 5.0, 6.5, 8.0, and 10.0 m) at six different friction velocities (0.23, 0.35, 0.41, 0.47, 0.55, and 0.61 m/s). We atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In previous studies, mainly bed traps were used to measure creep transport rates (Bagnold, 1941; Cheng et al, 2015), and only very limited theoretical approaches for creep have been reported up to the present (Wang & Zheng, 2004). All proposed creep transport laws are either empirical or semiempirical, and lack a solid physical basis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, mainly bed traps were used to measure creep transport rates (Bagnold, 1941; Cheng et al, 2015), and only very limited theoretical approaches for creep have been reported up to the present (Wang & Zheng, 2004). All proposed creep transport laws are either empirical or semiempirical, and lack a solid physical basis.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we defined creep to be synonymous with reptation, as the terms are often used interchangeably [2][3][4][5][6] and there is no protocol for distinguishing the grain hops of creep from the grain hops of reptation. Compared to saltation, creep still remains an understudied transport phenomenon [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to explain the poor performance of aeolian sediment transport models in coastal environments, many authors emphasized the importance of bed surface properties. Typical bed surface properties that are found along the coast and assumed to explain at least partially the poor performance of aeolian sediment transport models are high moisture contents [e.g., Wiggs et al , ; Davidson‐Arnott et al , ; Darke and McKenna Neuman , ; McKenna Neuman and Sanderson , ; Udo et al , ; Bauer et al , ; Edwards and Namikas , ; Namikas et al , ; Scheidt et al , ], salt crusts [e.g., Nickling and Ecclestone , ], bed slopes [e.g., Iversen and Rasmussen , ], vegetation [e.g., Arens , ; Lancaster and Baas , ; Okin , ; Li et al , ; Dupont et al , ], shell pavements [e.g., van der Wal , ; McKenna Neuman et al , ], and sorted and armored beach surfaces [e.g., Gillette and Stockton , ; Gillies et al , ; Tan et al , ; Cheng et al , ]. The influence of these bed surface properties on aeolian sediment transport has been investigated and often resulted in modified values for the velocity threshold [e.g., Howard , ; Dyer , ; Belly , ; Johnson , ; Hotta et al , ; Nickling and Ecclestone , ; Arens , ; King et al , ].…”
Section: Introductionmentioning
confidence: 99%